(untitled) (KIUT Publication, 2025)
The article examines the prospects for interdisciplinary interaction between phthisiology, pulmonology and architecture in the context of creating modern medical institutions that meet both medical standards and energy efficiency requirements. Particular attention is paid to architectural solutions that improve the microclimate, ventilation and insolation in rooms intended for the diagnosis and treatment of respiratory diseases. Examples of domestic and foreign design of phthisiopulmonology centers are analyzed, taking into account sanitary and hygienic standards and principles of sustainable construction. The importance of integrating architectural innovations and clinical requirements to improve the quality of treatment, prevent nosocomial infections and reduce operating costs of medical institutions is emphasized.